Impact of controlled attenuation parameter on detecting fibrosis using liver stiffness measurement. Issue 7 (15th February 2018) - Karlas, T.; Petroff, D.; Sasso, M.; Fan, J.‐G.; Mi, Y.‐Q.; de Lédinghen, V.; Kumar, M.; Lupsor‐Platon, M.; Han, K.‐H.; Cardoso, A. C.; Ferraioli, G.; Chan, W.‐K.; et al.
Summary: Background: Liver fibrosis is often accompanied by steatosis, particularly in patients with non‐alcoholic fatty liver disease (NAFLD), and its non‐invasive characterisation is of utmost importance. Vibration‐controlled transient elastography is the non‐invasive method of choice; however, recent research suggests that steatosis may influence its diagnostic performance. Controlled Attenuation Parameter (CAP) added to transient elastography enables simultaneous assessment of steatosis and fibrosis. Aim: To determine how to use CAP in interpreting liver stiffness measurements. Methods: This is a secondary analysis of data from an individual patient data meta‐analysis on CAP. The main exclusion criteria for the current analysis were unknown aetiology, unreliable elastography measurement and data already used for the same research question. Aetiology‐specific liver stiffness measurement cut‐offs were determined and used to estimate positive and negative predictive values (PPV/NPV) with logistic regression as functions of CAP. Results: Two thousand and fifty eight patients fulfilled the inclusion criteria (37% women, 18% NAFLD/NASH, 42% HBV, 40% HCV, 51% significant fibrosis ≥ F2). Youden optimised cut‐offs were only sufficient for ruling out cirrhosis (NPV of 98%). With sensitivity and specificity‐optimised cut‐offs, NPV for ruling out significant fibrosis was moderate (70%) and could be improved slightly through consideration of CAP. PPV for significant fibrosis and cirrhosis were 68% and 55% respectively, despite specificity‐optimised cut‐offs for cirrhosis. Conclusions: Liver stiffness measurement values below aetiology‐specific cut‐offs are very useful for ruling out cirrhosis, and to a lesser extent for ruling out significant fibrosis. In the case of the latter, Controlled Attenuation Parameter can improve interpretation slightly. Even if cut‐offs are very high, liver stiffness measurements are not very reliable for ruling in fibrosis or cirrhosis. Abstract : Linked Content This article is linked to Hassan and Tapper and Karlas et al papers. To view these articles visit https://doi.org/10.1111/apt.14584 and https://doi.org/10.1111/apt.14632 .